The Gereja Sebagai Komunitas Inklusi: Refleksi Hidup Menggereja Bersama Penyandang Disabilitas - Paruru, Nofvrind (APOSTOLOS, 2024)
This article discusses the calling and involvement of the church as a faith community to become an inclusive community as a reflection of the church together with people with disabilities. The method used is a qualitative approach with library methods. Talking about disability also means talking about the body and the human bodily experience. The bodily experience in question is not only a physical matter, but the integrity of humans as bodily beings. The reality of normality which creates a distinction between "normal" and "abnormal" in society invites us to look deeper into the meaning of "body" from a theological perspective that cannot be separated from the concept of Imago Dei. Mapping approaches to people with disabilities can be an evaluation and reflection for the church to see to what extent the church is present in the midst of life together with people with disabilities. The conclusion of this article states that re-reading Biblical texts from a disability perspective by interpreting the "body" as a whole strengthens the church's commitment to living out its call, namely to be an inclusive community that is solidary and embraces people with disabilities.